Racial Differences in Relative Skeletal Muscle Mass Loss During Diet‐Induced Weight Loss in Women. Issue 8 (29th June 2018) - Hunter, Gary R.; Bryan, David R.; Borges, Juliano H.; David Diggs, M.; Carter, Stephen J.
Abstract : Objective: It is unclear whether there are race‐specific differences in the maintenance of skeletal muscle during energy restriction. Changes in relative skeletal muscle index (RSMI; limb lean tissue divided by height squared) were compared following (1) diet alone, (2) diet + aerobic training, or (3) diet + resistance training. Methods: Overweight, sedentary African American (AA; n = 72) and European American (EA; n = 68) women were provided an 800‐kcal/d diet to reduce BMI < 25 kg/m 2 . Regional fat‐free mass was measured with dual‐energy x‐ray absorptiometry. Steady‐state VO2 and heart rate responses during walking were measured. Results: AA women had greater RSMI and preserved RSMI during diet alone, while RSMI was significantly reduced among EA women (EA women –3.6% vs. AA women + 1.1%; P < 0.05). Diet + resistance training subjects retained RSMI (EA women + 0.2% vs. AA women + 1.4%; P = 50.05), whereas diet + aerobic training subjects decreased RSMI (EA women –1.4% vs. AA women –1.5%; P < 0.05). Maintenance of RSMI was related to delta walking ease and economy. Conclusions: Compared with AA women, EA women are less muscular and lose more muscle during weight loss without resistance training. During diet‐induced weight loss, resistance training preserves skeletal muscle, especially among premenopausal EA women. Maintenance of muscle during weight loss associates with better ease and economy of walking.